Can we become friends? Students’ cross-racial interaction in post-apartheid South African higher education (Journal of Student Affairs in Africa, 2021)
This article investigates and documents how undergraduate students in South Africa make meaning of cross-racial interaction on the college campus in the post-apartheid era. Additionally, it explores how students perceive that interactions with diverse peers have shifted since apartheid, and how these interactions are indicative of the larger social dynamic of South Africa. Utilising Jansen’s (2009) framework for understanding Afrikaner student perspectives and Critical Race Theory (CRT), this qualitative exploration collected interviews from 10 students at a higher education institution (HEI) in South Africa. Findings identified three overarching themes found among students including contradiction within and across racial groups, Afrikaner white vs. English white and racial segregation on campus. These themes directly correspond with personal and societal aspects that influence meaning making in South Africa, including intrapersonal and interpersonal dynamics, historical legacy and institutional structures.
Keywords: Student affairs; diversity; student housing; application and selection process; social contact theory; higher education